A polymethoxy flavonoids‐rich Citrus aurantium extract ameliorates ethanol‐induced liver injury through modulation of AMPK and Nrf2‐related signals in a binge drinking mouse model. (14th July 2015) - Choi, Bong‐Keun; Kim, Tae‐Won; Lee, Dong‐Ryung; Jung, Woon‐Ha; Lim, Jong‐Hwan; Jung, Ju‐Young; Yang, Seung Hwan; Suh, Joo‐Won
<x xml:space="preserve">Abstract</x> Nobiletin and tangeretin are polymethoxy flavonoids (PMFs), found in rich quantities in the peel of citrus fruits. In the present study, we assessed the biological effect of the PMFs on liver damage using a mouse model of binge drinking. First, we extracted PMFs from the peels of Citrus aurantium to make Citrus aurantium extract (CAE). Male C57BL/6 mice were orally treated with silymarin and CAE (50, 100, and 200 mg/kg) for 3 days prior to ethanol (5 g/kg, total of 3 doses) oral gavage. Liver injury was observed in the ethanol alone group, as evidenced by increases in serum hepatic enzymes and histopathologic alteration, as well as by hepatic oxidative status disruption. CAE improved serum marker and hepatic structure and restored oxidative status by enhancing antioxidant enzyme levels and by reducing lipid peroxidation levels. In addition, CAE evidently suppressed inflammation and apoptosis in the livers of mice administered with ethanol, by 85% (tumor necrosis factor‐α) and 44% compared to the control group, respectively. Furthermore, CAE activated lipid metabolism related signals and enhanced phosphorylation of AMP‐activated protein kinase (AMPK) and nuclear factor E2‐related factor 2 (Nrf2) with several cytoprotective proteins including heme oxygenase‐1, NAD(P)H quinone oxidoreductase 1, and γ‐glutamylcysteine synthetase. Taken together, the present study demonstrated that, CAE possesses antioxidant, anti‐inflammatory, and antiapoptotic activity against ethanol‐induced liver injury. Copyright © 2015 John Wiley & Sons, Ltd.